POST-PANDEMIC TOURISM: OPPORTUNITIES FOR CREATIVE TOURISM: Received: 28thJuly 2022; Revised: 27thSeptember 2022, 3rd October 2022, 21st October 2022; Accepted: 28th October 2022 - Cabeca, Sonia Moreira (PEOPLE: International Journal of Social Sciences, 2022)
Tourism was one of the most affected sectors by the outbreak of COVID-19 in early 2020, and the travel sector has faced a dramatic challenge, with the pandemic’s devastating impact on the economy. In tourism, as in other sectors, there is a pre-pandemic and post-pandemic era, and several researchers are now trying to comprehend the future of tourism in a post-pandemic world. In this exploratory text, based on a literature review, we question if creative tourism can play a major role in the rebuilding of the tourism industry, once it is a type of tourism that relies on place-based experiences that uses local resources and involves communities and tourists in immersive activities. In fact, creative tourism seems to be a response to the challenges that actual tourism is facing, namely the change in the tourists’ perception about physical distancing, the need to avoid over tourism, mass tourism and touristification, the desire to reconnect with other people and to have enriching emotional experiences, the increase of awareness about sustainability (for places and future generations) and about the resident’s needs and their living conditions degradation. Our approach relates the ongoing research on post-pandemic tourism, from several points of view – the tourist’s perceptions and demands, the communities and territories’ needs, and the new visions of tourism planners… – with creative tourism, addressing the new opportunities for such type of tourism, and questioning its feasibility and potential contribution to a more meaningful tourism for both hosts and guests, to local economies growth, and overall, to making tourism a more sustainable industry.